The Role of Artificial Intelligence and Blockchain Technology in Crisis Management, Startup Growth, and Sustainable Future - Sharma, Asha; Mishra, Aditya (American Journal of Business Science Philosophy, 2025)
This study examines the impact of artificial intelligence (AI) and blockchain technology on crisis management, startup growth, and sustainability in the Indian business landscape. Using a quantitative, cross-sectional research design, data was collected from 123 research and development (R&D) employees across various enterprises. The study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze relationships between key constructs. The results indicate that AI plays a crucial role in enhancing crisis management and business resilience (β = 0.553, p = 0.000), while effective crisis management positively influences long-term sustainability (β = 0.272, p = 0.000). Additionally, blockchain technology is a key driver of startup growth (β = 0.684, p = 0.000), and growing startups significantly contribute to a sustainable future (β = 0.689, p = 0.000). The findings highlight the transformative potential of AI and blockchain in navigating business uncertainties, fostering innovation, and driving sustainable development. The study offers practical implications for business leaders, policymakers, and entrepreneurs in leveraging emerging technologies for long-term resilience and success.
Keywords: artificial intelligence; blockchain technology; crisis management; startup growth